2019
DOI: 10.1371/journal.pone.0219539
|View full text |Cite
|
Sign up to set email alerts
|

Increased methotrexate intolerance in juvenile idiopathic arthritis compared to acute lymphoblastic leukaemia in children

Abstract: Objectives To analyse the internal consistency of an adaption of the methotrexate intolerance severity score (MISS); and to describe and compare the level of methotrexate intolerance evaluated by the MISS in Danish children with juvenile idiopathic arthritis (JIA) or acute lymphoblastic leukaemia (ALL), treated with low-dose methotrexate (MTX). Methods Cross-sectional study of children diagnosed with JIA or ALL, treated with low-dose MTX, aged 9 years or above, and cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Methotrexate intolerance may be particularly evident among children with JIA [ 50 ], and there seems to be a strong positive association between side effects of methotrexate and needle pain [ 51 , 52 ]. This intolerance was not the main topic in this study, but findings indicated that intolerance played an important role in children’s experiences with needle injections.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate intolerance may be particularly evident among children with JIA [ 50 ], and there seems to be a strong positive association between side effects of methotrexate and needle pain [ 51 , 52 ]. This intolerance was not the main topic in this study, but findings indicated that intolerance played an important role in children’s experiences with needle injections.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate intolerance may be particularly evident among children with JIA (49), and there seems to be a strong positive association between side effects of methotrexate and needle pain (50,51). This intolerance was not the main topic in this study, but ndings indicated that intolerance played an important role in children's experiences with needle injections.…”
Section: Building Con Dence In Everyday Lifementioning
confidence: 62%